Operative Treatment of Idiopathic Isolated Clitoromegaly – A Clinical Case - Stoyanov S.; Ivanova K.; Koleva I. (Acta Medica Bulgarica, 2024)
Idiopathic clitoromegaly is a relatively rare disease. A case of isolated idiopathic clitoromegaly is presented. It concerns a 31-year-old woman, in whom the clitoris has showed a tendency for progressive enlargement in the last 3-4 years. The patient had no gynecological and systemic diseases and disorders. Karyotype and hormone levels were normal. No cystic changes in the ovaries and other changes in the abdominal organs were detected during ultrasound. Computerized axial tomographic (CAT) scan of the adrenal glands was performed and showed normal appearance. Method of selection in such cases is operative treatment – clitoroplasty with storage of neurovascular bundle of the clitoris.